Catheter interventional treatment of congenital portosystemic venous shunts in childhood. Issue 7 (30th December 2015) - Knirsch, Walter; Benz, Dominik C.; Bühr, Patrick; Quandt, Daniel; Weber, Roland; Kellenberger, Christian; Braegger, Christian P.; Kretschmar, Oliver
Abstract : Objectives: The study aimed on the catheter interventional treatment of congenital portosystemic venous shunt (CPSVS) in childhood and the impact on vascular growth of hypoplastic portal veins. Clinical course and follow up of partial or complete closure of CPSVS are described. Background: CPSVS is a very rare vascular malformation of the portal venous drainage resulting in potentially life threatening abdominal, pulmonary, cerebral, and cardiac complications. The anatomic type, clinical course, and diagnosis must be determined for optimal management. Methods: Single centre case series. Results: Eight (6 female) children with extrahepatic ( n = 5) and intrahepatic ( n = 3) CPSVS were diagnosed invasively by catheterization, including test balloon occlusion of the shunt and simultaneous retrograde angiography, and treated by catheter interventions ( n = 5) with partial ( n = 2) and complete ( n = 3) occlusion of CPSVS at a median age of 3.9 years (range 0.7–21). Congenital heart disease (CHD) was the most frequent associated organ manifestation ( n = 5) followed by mild to severe pulmonary arterial hypertension ( n = 4), hepatopulmonary syndrome ( n = 2), and portosystemic encephalopathy ( n = 1). CHD was simple ( n = 3) or complex type ( n = 2). Three patients were untreated so far, because they were in excellent clinical condition at an age <1 year, refused treatment, or planned for later treatment. Conclusions: Accurate invasive diagnosis of CPSVS with test balloon occlusion of the shunt is mandatory to depict the anatomic situation. Catheter interventional treatment of CPSVS offers a feasible and safe approach with complete or partial closure of the vascular malformation inducing potentially significant vascular growth of a former hypoplastic portal venous system. © 2015 Wiley Periodicals, Inc.